Acute effects of static and ballistic stretching on measures of strength and power - Samuel, M. N.; Holcomb, W. R.; Guadagnoli, M. A.; Rubley, M. D.; Wallmann, H. (The Journal of Strength and Conditioning Research, 2008)
Preactivity stretching is commonly performed by athletes as part of their warm-up routine. However, the most recent literature questions the effectiveness of preactivity stretching. One limitation of this research is that the stretching duration is not realistic for most athletes. Therefore, the purpose of this study was to determine the effects of a practical duration of acute static and ballistic stretching on vertical jump (VJ), lower-extremity power, and quadriceps and hamstring torque. Twenty-four subjects performed a 5-minute warm-up followed by each of the following three conditions on separate days with order counterbalanced: static stretching, ballistic stretching, or no-stretch control condition. Vertical jump was determined with the Vertec VJ system and was also calculated from the ground-reaction forces collected from a Kistler force plate, which also were used to calculate power. Torque output of the quadriceps and hamstrings was measured through knee extension and flexion on the Biodex System 3 Dynamometer at 60[degrees][middle dot]s-1. Data normalized for body weight were analyzed using five separate, 3 (stretch condition) x 2 (gender) analysis-of-variance procedures with repeated measures on the factor of stretch condition. The gender x stretch interaction was not significant for any of the four measures, suggesting that the stretching conditions did not affect men and women differently. The results of this study reveal that static and ballistic stretching did not affect VJ, or torque output for the quadriceps and hamstrings. Despite no adverse effect on VJ, stretching did cause a decrease in lower-extremity power, which was surprising. Because of the mixed results, strength coaches would be better served to use dynamic stretching before activity; this has been consistently supported by the literature.